Surveying the quality of prehospital emergency services for the elderly falls 2017 - Morteza Ghaderi Azarkhavarani; Negin Masoudi Alavi (Journal of Education and Health Promotion, 2018)
INTRODUCTION: Falls are the most common cause of injuries in elderly population. This study aimed to determine the quality of prehospital emergency services (EMS) for the elderly falls in 2017. MATERIALS AND METHODS: This cross-sectional study was carried out at the Pre-hospital Emergency Center of Kashan in 2017. The sample consisted of elderly people who had reported fall incidents in EMS. The questionnaire consisted of 7 areas with 54 items. Data collected by descriptive and inferential statistics of Friedman and Mann–Whitney were analyzed by SPSS v. 16 software. RESULTS: The number of elderly people was 150 (58% female) and the average age was 68.22 ± 6.75 years. Most falls (88.65%) occurred at home. The average performance scores (between 0 and 2) were as follows: assessment of the scene of the incident (1.51), primary assessment of the elderly (1.46), airway management (1.64), circulation management (1.78), fixation (1.82), secondary and continuous assessment (1.59), and patient transfer (1.68). It was found that secondary assessment and transfer of the male patients were significantly higher in quality than female patients (P < 0.05). CONCLUSIONS: In this research, the quality of care in all areas was reported to be desirable. It is recommended that the weaknesses of each area are investigated and the necessary strategies are taken into account such as staff training, changes in data collection forms, and training for the elderly.